Haji, Ibadah Holistik, dan Unik - Imam Hendriyadi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2019)
Hajj is a religious activity that has a religious dimension. Hajj is obligatory (forthose who can afford) specified in the law. Hajj is an Islamic Rukum to five. Hajjhas the actualization of worship and moral-social values remarkable. Haji kind ofworship that drive elements and also Maliyah badaniyah (possessions). Thereforesome scholars argued that the Hajj is the main worship (afdlal). Although othersargue that the most important is prayer, or the recollection of God, or jihad fisabilillahKata Kunci: Haji, Ibadah Holistik, Unik